Quantum few-body systems : proceedings of the Joint Physics/Mathematics Workshop on Quantum Few-Body Systems, Aarhus, Denmark, 19-20 March 2007 - Joint Physics/Mathematics Workshop on Quantum Few-Body Systems (2007 : Aarhus, Denmark); Moller, Jacob S.; Federov, Dmitiri (Melville, N.Y. : American Institute of Physics)
Includes bibliographical references and author index